Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1155/2020/3095672
|View full text |Cite
|
Sign up to set email alerts
|

“Buy Online, Pick Up in Store” under Fit Uncertainty: To Offer or Not to Offer

Abstract: Retailers offer BOPS (Buy Online, Pick Up in Store) service to improve consumers shopping experience. However, this greatly increases the decision complexity for retailers and consumers. For consumers, whether to purchase online or from a store with the BOPS service is a complex decision. This is especially true when the product has fit uncertainty. That is, consumers are uncertain about product fitness before using it. Also, their store visit cost can be heterogeneous and follows some distribution fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Retailing studies have found that the shopping environment (e.g., cleanliness, in-store air quality) affects consumers' purchasing behavior, and declining sales of stores are related to unpleasant circumstances (Kumar and Karande, 2000;Turley and Milliman, 2000;Nicholson et al, 2002;Chocarro et al, 2013;Kang et al, 2019). Meanwhile, evidence has shown that consumers have channel switching behavior among different channels (Reardon and McCorkle, 2002;Choi and Mattila, 2009;Avery et al, 2012;Kleinlercher et al, 2018;Li et al, 2020). Specifically, Reardon and McCorkle (2002) outlined that consumers' channel choices are influenced by five factors: the relative opportunity cost of time, the cost of products, the pleasure of shopping, the perceived value of products and the relative risk of channels.…”
Section: Literature Review and Hypothesis Development The Impact Of Air Pollutionmentioning
confidence: 99%
“…Retailing studies have found that the shopping environment (e.g., cleanliness, in-store air quality) affects consumers' purchasing behavior, and declining sales of stores are related to unpleasant circumstances (Kumar and Karande, 2000;Turley and Milliman, 2000;Nicholson et al, 2002;Chocarro et al, 2013;Kang et al, 2019). Meanwhile, evidence has shown that consumers have channel switching behavior among different channels (Reardon and McCorkle, 2002;Choi and Mattila, 2009;Avery et al, 2012;Kleinlercher et al, 2018;Li et al, 2020). Specifically, Reardon and McCorkle (2002) outlined that consumers' channel choices are influenced by five factors: the relative opportunity cost of time, the cost of products, the pleasure of shopping, the perceived value of products and the relative risk of channels.…”
Section: Literature Review and Hypothesis Development The Impact Of Air Pollutionmentioning
confidence: 99%